An analysis of codified corporate governance practices in the banking industry: The case study of Bangladesh - Suzuk Yasushi; A. K. M. Kamrul Hasan (e-Finanse: Financial Internet Quarterly, 2018)
Introducing a well-designed system of corporate governance is considered an effective tool to ensure the stability and resilience of a banking system. It was in 2006 when Bangladesh initiated its first corporate governance code (CG code). Despite trying to meet the code of enhancing the internal monitoring mechanisms and transparency in governance, it is apparent that the quality in bank credit portfolios continuously deteriorated. This paper aims to empirically analyze the impact of adopting the CG code on performance for eight years (2010-2017) of 21 major commercial banks of Bangladesh. In this case study, we suggest that the CG code may have given the Bangladeshi commercial banks an ill-incentive for the reduction of executive directors under the pressure of meeting a guideline to increase the ratio of independent directors. This incentive structure had a negative impact on bank performance during the period. Another finding is that the fundamental structure of ownership and control by sponsor directors remained unchanged during the period. This structure of maintaining the control of power by a group with its vested interest may have hindered the effectiveness of the CG code in Bangladesh. We suggest that the agenda of CG practices should go together with a policy for mitigating a potential bias under the ownership concentration because any attempt of adopting codified CG practices would be futile under the fundamental structure in Bangladesh.
Keywords: G34; G38; M48; 330; Corporate governance; corporate governance code; bank performance